IS MERGERS AND ACQUISITIONS OF INDIAN INDUSTRY GROWING POSITIVELY IMPACT DURING 1995 TO 2018? - Prabu, K A.Keerthi (International Journal of Psychosocial Rehabilitation, 2020)
The study seeks to investigate the impact of mergers and acquisitions (M&A’s) on operational performance on Indian industry during pre and post-merger period.In general, the aim of M&A’s is to attain economies of scale on the one hand, and increase market share on the other.In India, most of the studies were found on banking and finance and their focus were on the changes in profitability after M&A’s and very few studies were found examining any one or two of the performance indicators. In this perspective, the study makes an attempt to examine the mergers and acquisitions on physical parameters of Indian industries specifically pharmaceutical industry.